2013
DOI: 10.1007/s00268-013-1926-8
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Dosing and Survival in Adult Intensive Care Unit Patients

Abstract: Survival of patients with prolonged therapy with norepinephrine and epinephrine above the evaluated thresholds is poor, whereas short-term application of high-dose catecholamines is not associated with poor outcome. Therefore, it remains for the individual clinician, patients, and their surrogates to decide whether the use of high doses of vasopressors is appropriate in view of the low probability of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
3
19
0
1
Order By: Relevance
“…Only patients with septic shock requiring high-dose vasopressor (HDV) were included in the present study, as opposed to previous studies which included all types of shock [15, 17, 19, 22, 23]. In most instances, patients herein received norepinephrine exclusively, as recommended by the Surviving Sepsis Campaign [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only patients with septic shock requiring high-dose vasopressor (HDV) were included in the present study, as opposed to previous studies which included all types of shock [15, 17, 19, 22, 23]. In most instances, patients herein received norepinephrine exclusively, as recommended by the Surviving Sepsis Campaign [5].…”
Section: Discussionmentioning
confidence: 99%
“…Authors in previous studies have reported extremely high mortality rates in patients with shock and HDV, reaching upward of 94% [19]. Given the lack of common definition for refractory shock and high-dose vasopressor per se, there is considerable variability in administered dosages reported in the literature, ranging from 0.5 to 4 µg/kg/min [18, 19, 22, 24, 25]. Martin et al [16] recently established a refractory dosage of 1 µg/kg/min with a 90% mortality rate at D90.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of ‘do no harm’ needs to be balanced against the need to rescue blood pressure that would otherwise collapse instantly. The maximal NA dose is not incontrovertibly defined 2 4. Remarkably, the drug information source notes that patients in septic shock may require higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the drug dosage sections of two of the most widely accessed medical resources worldwide include the following information: (1) “Indication, hypotension, acute dose [weight-based dosing]: 0.02–1 μg/kg/min IV […]; Info: pts w/septic shock may require higher doses.” (Epocrates); and (2) “Sepsis and septic shock (weight-based dosing): Range from clinical trials: 0.01–3 μg/kg/min (Hollenberg, 2004)[…]” (Up To Date) 2 3. The evidence, criteria and reasoning for withholding further escalation of the dose (when the blood pressure continues to respond to increases in NA flow) are poorly described,4 and the relevant clinical data guiding practice are weak. A treating physician might wonder why further dosage escalations should not be attempted for a patient in whom the arterial pressure is maintained at an acceptable level with only increases in NA dosage, and who would otherwise certainly die.…”
Section: Introductionmentioning
confidence: 99%
“…Unjustified blood transfusions also carry the risk of hypervolemia and transmission of infections [14] or allergic reactions [15]. There is evidence that prolonged use of catecholamines is associated with poor outcome [16]. Therefore, it is important to recognize the point when tissue perfusion has normalized, and terminate resuscitation.…”
Section: Physiological Issuesmentioning
confidence: 99%